2000
DOI: 10.1016/s1042-4431(00)00041-x
|View full text |Cite
|
Sign up to set email alerts
|

Central bank intervention and exchange rates: the case of Sweden

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…They also found-unlike the present paper-that larger interventions had a higher probability of success than small interventions. On the other hand, our results are similar to those of Aguilar and Nydahl (2000), who also found that Swedish interventions were generally ineffective. Note: We chose these sample periods to correspond with those in tables 3 through 6.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…They also found-unlike the present paper-that larger interventions had a higher probability of success than small interventions. On the other hand, our results are similar to those of Aguilar and Nydahl (2000), who also found that Swedish interventions were generally ineffective. Note: We chose these sample periods to correspond with those in tables 3 through 6.…”
Section: Discussionsupporting
confidence: 90%
“…Our overall results are similar to Aguilar and Nydahl (2000), the only other paper to study official Riksbank intervention during the krona float. 2 They investigated daily interventions in Swedish kronor against German marks and U.S. dollars from January 7, 1993, to December 30, 1996, using a multivariate extension of the GARCH-M model and found little evidence that Riksbank interventions affected either the level or the volatility of day-to-day, krona-dollar or krona-mark exchange rates.…”
Section: Introductionsupporting
confidence: 87%
“…Over the past two decades, the effects of central bank interventions in foreign exchange markets on exchange rate volatility have been the focus of a number of empirical studies (see, e.g., Dominguez 1998 andAguilar/Nydahl 2000). Researchers have not only been interested in the magnitude of the effect of central bank interventions on exchange rate volatility but also in the sign of this effect.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, for the whole period (1977)(1978)(1979)(1980)(1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994) central bank intervention generally leads to higher exchange rate volatility. Aguilar and Nydahl (1998) investigate the impact of interventions on the level and volatility of the Swedish Krona (SEK) /USD-and SEK/DEM-rate from January 1993 to November 1996, a period when the SEK was floating. A bivariate GARCH-framework and as a second approach, implied volatilities from currency options were used.…”
Section: Empirical Evidence In the Literaturementioning
confidence: 99%
“…2 There are few other papers dealing with different currency pairs: Fischer and Zurlinden (1998) with the CHF/USD exchange rate, Aguilar and Nydahl (1998) with the USD/SEK and DEM/SEK exchange rates. Mundaca (1993) analyzed the NOK against a trade-weighted basket of foreign currencies and against the ECU.…”
mentioning
confidence: 99%